The street as a space for care production: the singular therapeutic project and tuberculosis management in people experiencing homelessness during the Covid-19 pandemic in the city of Rio de Janeiro - Aline Azevedo Vidal; Karla Santa Cruz Coelho; Emerson Elias Merhy (Salud Colectiva, 2024)
From the theoretical perspective of the cartography of the micropolitics of living labor in action, the objective was to analyze the work process of the “street clinic” team based in a primary care unit in the city of Rio de Janeiro, Brazil, in the management of tuberculosis cases in the context of the Covid-19 pandemic. This is an exploratory qualitative research. Between May and December 2021, seven professionals from the street clinic team were interviewed, and participant observation was conducted with field diary records. Three thematic axes emerged from the interviews related to people experiencing homelessness in the context of the Covid -19 pandemic: 1) Challenges, potentialities, and weaknesses of tuberculosis care; 2) Building intersectoral care networks for monitoring individuals with tuberculosis; and 3) The street as a space for care production: the work process of the street clinic in tuberculosis management. It is concluded that caring for people experiencing homelessness with tuberculosis in the context of the Covid -19 pandemic requires not only managing clinical protocols but also building shared work with the intra and intersectoral network. In addition to the task of being in the territory, the outpatient service in the territory must also be a street outpatient service, especially regarding tuberculosis treatment.